Strategi Kesiapan Aparatur dan Budaya Kerja Terhadap Kualitas Layanan Informasi Melalui Pemanfaatan Aplikasi Devakad di Prodi Pendidikan Administrasi Perkantoran Universitas Negeri Medan - Andika Rifky Maulana; Dina Rosanna Sipahutar; Lia Ima Triwani Siahaan; Muhammad Khadafi Chaniago (Jurnal Administrasi Perkantoran, 2025)
This research aims to analyze apparatus readiness strategies and work culture on information service quality through DEVAKAD application utilization in the Office Administration Education Study Program, State University of Medan. Qualitative descriptive approach employed observation, structured interviews with one DEVAKAD manager and three final-year students, and document analysis at the study program office in November 2025. Findings reveal apparatus possess strong technical readiness in document verification and issue response, supported by adaptive work culture accelerating digital services despite incomplete dynamic information. Conclusion confirms significant positive influence of apparatus readiness and work culture on DEVAKAD effectiveness. Recommendations include ongoing training and innovation-oriented culture reinforcement; implications enhance transparency, good governance efficiency, and academic user satisfaction. Keyword: readiness of the apparatus; work culture; DEVAKAD; information services; academic administration.